EARLY CHILDHOOD LANGUAGE POLITENESS STRATEGY MODEL IN MULTIETHNIC COMMUNICATION - Dian Eka Chandra Wardhana; Noermanzah Noermanzah (English Review: Journal of English Education, 2021)
The purpose of this study is to describe the strategy model of early childhood language politeness in multi-ethnic communication with different social rules in Bengkulu. The research method used was a cross-sectional study design, with a study of subjects of different ages. The research subjects referred to were children aged 2, 3, 4 and 5 years in Bengkulu. Data collection was carried out by participating and non-participating observations, accompanied by data recording using an electronic recording device and field note cards. Data analysis was performed using flow analysis techniques. The results show that the strategy model for early childhood language politeness in multi-ethnic communication in Bengkulu is using elaborate politeness acquisition model and children's language politeness acquisition model that takes into account social distance when speaking by stringing 3 words when greeting, introducing oneself, expressing respect, thanking. love, apologize, ask permission, ask for help, ask for things, command, and promise. The series of words are meant to reflect the character development of early childhood.